Conciliation : The End of Compulsory Boards - Cunningham, W. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1970)
The Woods' Report has recommended the abolition of compulsory conciliation boards. The recent de-emphasis on compulsory conciliation boards in the provinces of Nova Scotia, New Brunswick and Ontario by legislative changes and administrative practices has led to certain conclusions. Experience has shown that the benefits to collective bar-gaining hâve been désirable, and that the incidence and/or magnitude of strikes hâve not increased.